Speculative Growth: Hints from the U.S. Economy - Caballero, RicardoJ.; Farhi, Emmanuel; Hammour, MohamadL. (American Economic Review, 2006)
We propose a framework for understanding episodes of vigorous economic expansion and extreme asset valuations. We interpret this phenomenon as a high-valuation equilibrium with a low cost of capital based on optimism about future funding. The key ingredient for such equilibrium is feedback from increased growth to a decline in the long-run cost of capital. This feedback arises when an expansion comes with technological progress in the capital sector, when fiscal rules generate procyclical fiscal surpluses, when the rest of the world has lower expansion potential or high saving needs, and when financial constraints are relaxed by the expansion itself.